Twenty-year trends in heart failure among U.S. adults, 1999–2018: The growing impact of obesity and diabetes. (1st September 2022) - Ciardullo, Stefano; Cannistraci, Rosa; Mazzetti, Simone; Mortara, Andrea; Perseghin, Gianluca
Abstract: Background: The aim of this study is to evaluate trends in heart failure (HF) prevalence, impact of accompanying risk factors and use of effective therapeutic regimens during the last two decades in the general adult US population. Methods: We analyzed data obtained from the 1999–2018 cycles of the National Health and Nutrition Examination Survey (NHANES). Among a total of 34, 403 participants 40 years or older who attended the mobile examination center visit, 1690 reported a diagnosis of HF. Trends in participant features across calendar periods were assessed by linear regression for continuous variables and logistic regression for binary variables. Results: Prevalence of self-reported HF did not change significantly from 1999 to 2002 to 2015–2018 ( 3.5%), while obesity and diabetes showed a progressive increase in prevalence, affecting 65% and 45% of patients with HF in the most recent calendar period, respectively. In parallel, use of glucose lowering drugs (especially metformin and insulin) as well as statins increased from 1999 to 2010, with significant improvement of the lipid control. A modest improvement in blood pressure control was achieved in association with a significant increase in the use of angiotensin receptor blockers and beta-blockers. Conclusions: In the last 20 years, the prevalence of HF in US adults remained stable, while both obesity and diabetes increased, with the two conditions affecting half of patients with HF. Improvements in the control of dyslipidemia and, to a lesser extent, blood pressure, was detected; nonetheless, a significant gap remains in guideline-directed use of HF and diabetes medications. Highlights: Heart failure is one of the most frequent causes of hospitalization among elderly individuals. We report the trend in heart failure prevalence in the United States in the last 20 years and evaluate the impact of metabolic comorbidities. We show that between 1999 and 2018, prevalence of HF remained constant in the adult US population, while among patients with HF prevalence of both diabetes and obesity increased progressively. A significant gap remains in guideline-directed use of heart failure treatments and awareness of this problem needs to increase among physicians.